2007
DOI: 10.1038/sj.onc.1210791
|View full text |Cite
|
Sign up to set email alerts
|

Integration of the HPV16 genome does not invariably result in high levels of viral oncogene transcripts

Abstract: Virus integration into the host genome is a characteristic step during cervical carcinogenesis. Experimental data provide evidence that integration could result in increased levels of oncogene (E6/E7) transcripts. This is the first study in which the level of viral transcripts is correlated to the physical state of the viral genome in cervical intraepithelial neoplasia (CIN) and cervical carcinomas (CxCa). Using the APOT-assay integrate-derived transcripts only were detected in 3/28 (11%) CIN and in 28/55 (51%… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
87
3
2

Year Published

2008
2008
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 112 publications
(100 citation statements)
references
References 39 publications
7
87
3
2
Order By: Relevance
“…Referring to a potential function of alternative splicing, however, examination of clinical samples has shown that the prevalence of the E6* mRNA isoform apparently increases with lesion severity, being finally the most abundant viral transcript found in cervical cancer cells and cell lines derived there from (10,25).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Referring to a potential function of alternative splicing, however, examination of clinical samples has shown that the prevalence of the E6* mRNA isoform apparently increases with lesion severity, being finally the most abundant viral transcript found in cervical cancer cells and cell lines derived there from (10,25).…”
Section: Discussionmentioning
confidence: 99%
“…In a second selection step, cells with preferential E6 exon exclusion and high E7 expression gain a selective growth advantage during pro-gression (40), providing a reliable explanation for the prevalence of E6* mRNA found in most cervix carcinoma cell lines and CIN lesions (10,25). Analyzing the E6*/E6 ratio in two well-established HPV16 positive cervical carcinoma cells, both expressing mainly E6*, only SiHa cells showed a moderate isoform shift toward fulllength E6 after EGF addition, whereas CaSki cells were not responding (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…13,14 Although virus positivity predicts a favorable outcome for TSCC, viral status in integrated or episomal forms and viral DNA load do not invariably correlate with the levels of viral oncogene transcripts, cell cycle protein expression, and prognosis. 15,16 CCRT will further complicate regulation of cell cycle, repair of DNA, and induction of apoptosis. Thus, it is worth identifying the extent to which the EBV existence and/ or HPV presence or integration by themselves or each by itself, and/or the p53, pRb, and/or p21 expression altered by virus and/or by chemical mutagens contribute to prognosis.…”
mentioning
confidence: 99%
“…It is believed that the integration arises in high grade lesions, such as CIN2 and CIN3 and the deregulation of E6 and E7 expression may increase or remain at a constitute level. [92,93] In this scheme, flat warts can be resembled in CIN1 lesions, however the proliferation level of the cell is lower in the basal and parabasal layers. [13] Increased expression levels of E6 and E7 in high-risk HPV type infections causes CIN2+ phenotypes.…”
Section: Lower Genital Tract Neoplasias: Cervical Vaginal and Vulvarmentioning
confidence: 99%